2020
DOI: 10.21608/ebwhj.2020.73814
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between antimullerian hormone level before and after laparoscopic ovarian autologous PRP injections

Abstract: Aim: Randomized clinical trial aimed to know the possible correlation between laparoscopic ovarian autologous PRP injection and AMH level. Patients and Methods: Fifty-one Sudanese subfertile women attended to Banoon Fertility Center, Khartoum, Sudan, during the period from January 2018-June 2019 selected randomly and exposed to laparoscopic ovarian autologous PRP injection. AMH level of every participant measured before and after 3 months of administration of PRP to the ovaries. Results and Conclusion:We measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Melo et al conducted a prospective controlled, nonrandomized comparative study in Venezuela on 46 women with low ovarian reserve prior to assisted reproductive technology (ART). 12 The mean BMI was 24.6±1.2 kg/m 2 , within normal limit as like present study. They investigated the impact of a 3-month course of intra cortical injections of autologous PRP upon ovarian reserve markers versus no intervention in women with low ovarian reserve.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Melo et al conducted a prospective controlled, nonrandomized comparative study in Venezuela on 46 women with low ovarian reserve prior to assisted reproductive technology (ART). 12 The mean BMI was 24.6±1.2 kg/m 2 , within normal limit as like present study. They investigated the impact of a 3-month course of intra cortical injections of autologous PRP upon ovarian reserve markers versus no intervention in women with low ovarian reserve.…”
Section: Discussionsupporting
confidence: 84%
“…The findings of this study are in accordance with Melo et al who found significant (p<0.001) improvement of post-PRP, AMH level at three month of ovarian PRP in 63.00% of participants. 12 AFC on ultrasound following PRP treatment increased in 75.00%. FSH level dropped in 33.00% of the women receiving PRP.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation